Design of Fiber Optic-Based Trainer Module with Bus Topology Method Using Optical Distribution Point - Aqilla, Syifa; Maria, Popy; Firdaus, Firdaus; Asril, Aprinal Adila (JATAED: Journal of Appropriate Technology for Agriculture, Environment, and Development, 2025)
The fiber optic based trainer module designed for Politeknik Negeri Padang, especially in the Telecommunication Engineering Study Program for the Fiber Optic Communication System course, aims to improve students' understanding of optical fiber. This module provides an opportunity for students to practice optical fiber splicing and identify problems in the bus topology directly. The module design includes a block diagram showing the components and tools used, including an HLS (Heights Light Source) to provide the input signal and an OPM (Optical Power Meter) to measure the optical power at the Optical Distribution Point (ODP). Measurements are made to ensure attenuation in accordance with the predetermined link budget value: ODP1 with passive splitter 1:2 (8.0007 dB), ODP2 with passive splitter 1:4 (18.4517 dB), ODP3 with passive splitter 1:4 (28.9035 dB), and ODP4 with passive splitter 1:4 (38.555 dB). The measurement results show that correctly performed splicing results in attenuation below the link budget value. However, in ODP1, the disconnection of the pigtail caused the attenuation to exceed the link budget value by -50.00 dBm. The module proved to be effective in teaching but requires more attention to pigtail maintenance and the addition of a troubleshooting guide to improve its reliability.